PENTINGNYA BUDIDAYA TANAMAN APOTEK HIDUP DILINGKUNGAN DESA KARANG GADING DALAM MENJAGA IMUNITAS TUBUH SELAMA PANDEMI COVID-19 - K. Afni; N. Hasanah; L. Saputri3; D. R Sitepu; Mardiati Mardiati; I Wirevenska (Jurnal Pengabdian Mitra Masyarakat, 2022)
The purpose of this service is to introduce live pharmacies to certain groups of people and to convey information about the benefits of living pharmacies in the yard of the house as a material to use to maintain body immunity during the Covid-19 pandemic. The method used in this community service is counseling in the form of providing education by explaining how important it is for us to plant live pharmacy plants and their benefits during the COVID-19 pandemic and then invite these residents to participate in the implementation of planting live pharmacies in the village. The selected target community is the Karang Gading Village Community, Kec. Kab. Stabat. Langkat. The results of this activity can make local residents better understand how to cultivate herbal plants and their uses.